PENINGKATAN KEDISIPLINAN KULIAH MELALUI KONSELING KELOMPOK PADA MAHASISWA SEMESTER III PROGRAM STUDI BIMBINGAN DAN KONSELING FKIP UNISRI TAHUN AKADEMIK 2012/2013 - Suryanti, Hera Heru Sri; Hartini, Sri - (UNIVERSITAS SLAMET RIYADI, 2013)
Abstract:This study aims to find out how to increase Giving Counseling Through the Discipline Study Group on Student Guidance and Counseling Program Guidance and Counseling UNISRI TA 2012/2013?. This research is a kind of action research Empirical (PTEM) the implementation procedures as follows: 1.Assigning a type of treatment (intervention)2. Recording data. 3. Assess the results. 4. Utilizing the results of the evaluation of the intervention program. Subjects were third semester students Study guidance and counseling program as FKIP UNISRI and research object is the improvement of discipline college student of Guidance and Counselling SemesterIII FKIP UNISRI TA 2012/2013. Result: The members are very enthusiastic group counseling in any implementation of counseling, his face radiated that they are happy and proud to note lecturers. Through the implementation of group counseling is an attitude of students who lack the discipline to follow lectures gradually changed. After counseling, the two existing 2 students were changed, after counseling, there are three to four students were changed, after counseling to all students consisting of six 7 people have changed. Â Keyword: Discipline, lectures, group counseling.